2014
DOI: 10.1093/ndt/gfu362
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomes in the diagnosis of Gitelman and Bartter syndromes

Abstract: UE phenotyping may be useful in the diagnosis of GS and BS, thus providing an alternative/complementary, urine-based diagnostic tool for SLT patient recognition and a diagnostic guidance in complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…In humans, urinary extracellular vesicles (uEVs), including exosomes, have been extensively characterized and studied as non-invasive biomarkers for renal tubular disorders [2528]. uEVs are nanosized membranous vesicles released from all cells lining the nephron.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, urinary extracellular vesicles (uEVs), including exosomes, have been extensively characterized and studied as non-invasive biomarkers for renal tubular disorders [2528]. uEVs are nanosized membranous vesicles released from all cells lining the nephron.…”
Section: Introductionmentioning
confidence: 99%
“…The cargo of uEVs reflects changes in the expression of different proteins present in the epithelial cells of the nephron, including the total and phosphorylated forms of NCC [20,67,68]. Indeed, it has been demonstrated that patients with Gitelman syndrome display a decreased NCC abundance in uEVs [67,69]. On the other hand, patients with Gordon syndrome show higher levels of NCC in the kidney and this increased abundance was also observed in the uEVs [68].…”
Section: The Role Of Nccsv In (Patho)physiologymentioning
confidence: 99%
“…Other groups have used exosome analysis to quantify NCC expression in response to high and low salt diets [217], and in limited fashion pNCC in patients with primary aldosteronism [216]. A recent study looked at NCC and NKCC2 expression in patients with Gitelman and Bartter syndrome [228]. The investigators found very low or undetectable NCC in exosomes of patients with Gitelman syndrome and similarly low levels of NKCC2 in patients with Bartter syndrome as compared with control subjects.…”
Section: What Are Urinary Exosomes and How Do We Isolate Them?mentioning
confidence: 99%
“…Mayan et al loaded western blot samples with a quantity of protein representing an amount of urine containing 3mg of creatinine [187]. Corbetta et al used standard amounts of protein on their gels, but expressed density per mg of creatinine to standardise [228]. Esteva-Font et al normalised human samples to creatinine and animal samples to time in one study [217], as did the study by van der Lubbe et al [216].…”
Section: Normalisation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation